The influence of transparency, accountability, human resource competence, technological innovation, and public participation on local government financial performance - Aziz, Syahidallazi; Wediyanto, Eko (Priviet Social Sciences Journal, 2024)
Public administration and financial management are crucial aspects of ensuring effective and efficient governance. This study aims to analyze the influence of transparency, accountability, human resource (HR) competence, technological innovation, and public participation on the financial performance of local governments in Bengkulu. A quantitative approach was employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. Data were collected from 374 respondents, including civil servants, academics, and community members involved in local financial management. This study developed seven hypotheses to examine the relationships among the variables. The results indicate that transparency, accountability, and HR competence positively influence financial performance. Furthermore, technological innovation and public participation play significant roles in enhancing the effectiveness of local budget management. The findings also reveal that HR competence mediates the relationship between technological innovation and local government financial performance. The implications of this study provide insights for policymakers to strengthen local financial systems by improving transparency, accountability, and technology-driven innovation. Additionally, the findings serve as a reference for developing more participatory and sustainable public policies.